A Retrodictive Study of English Majors’ Language Motivational Dynamics: A Triangulation Approach - Xuemei Jiang; Chili Li (Universitas Sebelas Maret, 2025)
This study investigates the motivational dynamics of English majors by integrating retrospective plotting, interviews, and narrative inquiry. Through triangulation, the research identifies key patterns and underlying causes of motivational shifts among three learners, proposing targeted strategies for remotivation. Findings reveal that English majors’ motivational trajectories exhibit marked dynamic complexity and individual variation, shaped by a multifaceted system of interacting factors—including teacher influence, academic performance, assessment pressures, emotional states, and career prospects. The study highlights the importance of understanding these dynamics to support learners effectively. Practical implications suggest that educators can foster remotivation by guiding students toward constructive attribution patterns, regulating academic emotions, enhancing self-regulatory skills, and clarifying future aspirations.